2009
DOI: 10.1021/la902845j
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Amphiphile Self-Assembly Particles Composed of Gadolinium Oleate and Myverol: Evaluation as Contrast Agents for Magnetic Resonance Imaging

Abstract: Gadolinium oleate has been added at various concentrations to a Myverol inverse bicontinuous cubic phase forming system, and the potential of these systems as magnetic resonance imaging (MRI) contrast agents has been investigated. Differential scanning calorimetry (DSC), small-angle X-ray scattering (SAXS), and cryo-transmission electron microscopy (cryo-TEM) measurements on the Gd oleate/Myverol systems indicate that Gd oleate is at least partially incorporated within the cubic phase of Myverol. However, at G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Cubic and inverse hexagonal phases have also been highlighted as a new class of imaging agent . The unique constraints of the internal structure on the mobility of water in the aqueous channels of cubosomes and hexosomes have been shown to provide an enhanced magnetic resonance imaging (MRI) contrast upon loading with nitroxide or heavy metal contrast agents . As seen in Figure , the relaxivity of the mesophase‐hosted material, observed as T1 weighted contrast in the bottom left panel, exceeds that of Magnevist, the gold standard, currently clinically utilized contrast agent.…”
Section: Technological Applications Of Lipidic Lyotropic Liquid Crystmentioning
confidence: 99%
“…Cubic and inverse hexagonal phases have also been highlighted as a new class of imaging agent . The unique constraints of the internal structure on the mobility of water in the aqueous channels of cubosomes and hexosomes have been shown to provide an enhanced magnetic resonance imaging (MRI) contrast upon loading with nitroxide or heavy metal contrast agents . As seen in Figure , the relaxivity of the mesophase‐hosted material, observed as T1 weighted contrast in the bottom left panel, exceeds that of Magnevist, the gold standard, currently clinically utilized contrast agent.…”
Section: Technological Applications Of Lipidic Lyotropic Liquid Crystmentioning
confidence: 99%
“…In other recent developments, cubosomes are also being investigated for the containment of contrast agents for medical imaging applications [106][107][108], and capabilities as a cell-free bio-sensing platform [109]. Apart from drug delivery and biomedical applications, the use and application of lyotropic liquid crystalline nanostructured particles is also relevant within the food industry (e.g., solubilization of food bioactives within lyotropic liquid crystalline mesophases) [110,111] and agriculture industry (e.g., delivery of plant agrochemicals) [112].…”
Section: Applications Of Cubosomes In Nanotechnologymentioning
confidence: 99%
“…Studies suggested that the packing efficiency of MO molecules results in structures such as an inverse hexagonal phase, several inverse cubic phases, a lamellar phase, and a water-in-oil microemulsion phase (Fig. [27][28][29][30][31] The use of MO based self-assembly objects in drug delivery has gained signicant interest due to its Fig. 4,5 In recent years, an increasing number of studies have focused on MO and its biomedical applications.…”
Section: Introductionmentioning
confidence: 99%